Optimization of Orthopedic Treatment of Dentition Defects in Patients with Chronic Diseases of the Gastrointestinal Tract (Eurasian Research Bulletin, 2023)
An orthopedic dentist, choosing a material and method of prosthetics, should focus on the condition of periodontal tissues and digestive organs closely related to the oral cavity, since somatic pathology directly affects periodontal tissues and, therefore, largely determines the choice of method and materials for prosthetics.